Method for preparing manganese zinc ferrite material from industrial manganese sulfate waste
By using industrial manganese sulfate waste to replace trimanganese tetraoxide, combined with pre-firing and sintering technology, the problems of high energy consumption, high pollution and difficult manganese sulfate treatment in the preparation of manganese zeb ferrite materials are solved, and the preparation of high-performance materials is realized and environmentally friendly use of waste.
Patent Information
- Application Number
- CN202411345135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art has problems such as high energy consumption, high pollution, high cost and difficulty in handling manganese sulfate waste when preparing manganese sulfate ferrite materials, and the residue of sulfate in manganese sulfate affects the magnetic permeability performance.
Industrial manganese sulfate waste is used to replace trimanganese tetraoxide, and the temperature and time are controlled during pre-firing and sintering, and sulfate is eliminated to form high-performance manganese zeolite material.
The preparation cost of manganese zinc ferrite materials is reduced, the material performance and qualification rate are improved, and the effective treatment of manganese sulfate waste and the development of green energy-saving.
Smart Images

Figure BDA0005061820530000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic materials, and in particular to a method for preparing a manganese-zinc ferrite material by utilizing industrial manganese sulfate waste. Background Art
[0002] Manganese sulfate is a common industrial waste. A large amount of industrial manganese sulfate slag is produced in the process of industrial production of electrolytic manganese. Since manganese sulfate is a hazardous substance with strong toxicity and corrosiveness, random burial will damage soil and water bodies. Therefore, the utilization rate of manganese sulfate waste generated by my country's industry is low, and it is difficult to handle, which also brings great pollution to the environment. Improper handling will also threaten the lives and safety of the people. If these manganese sulfate slags can be processed and utilized and converted into industrial products, it will be of great significance to our environmental protection.
[0003] As a widely used electronic material, manganese-zinc ferrite material has many advantages such as high magnetic permeability, high saturation magnetic flux density, low power consumption, high superposition, high resistivity, etc., and is widely used in people's production and life. At present, the preparation of manganese-zinc ferrite material mainly uses industrial iron oxide, manganese tetraoxide and zinc oxide as raw materials, and is prepared into ferrite cores after mixing, pre-burning, sand grinding, molding and sintering. The industrial manganese tetraoxide used is obtained by burning manganese oxide, hydroxide, sulfate and carbonate in air or oxygen (1000℃). The production process has the disadvantages of high energy consumption, high pollution and high cost.
[0004] Manganese sulfate can be decomposed into manganese dioxide or manganese tetraoxide after heating, and these oxides are one of the raw materials needed to prepare manganese-zinc ferrite materials. However, since manganese sulfate also contains sulfate, the sulfate remains in the ferrite body, which can easily cause abnormal growth of grains during the subsequent sintering process, thereby affecting its magnetic permeability and other properties. Therefore, it is difficult to use manganese sulfate to prepare high-performance manganese-zinc ferrite materials. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a manganese-zinc ferrite material using industrial manganese sulfate waste. The present invention uses industrial manganese sulfate waste instead of manganese tetraoxide to prepare a manganese-zinc ferrite material, thereby reducing the preparation cost of the manganese-zinc ferrite material, and the obtained manganese-zinc ferrite material has excellent performance and a high qualified rate. At the same time, a large amount of industrial manganese sulfate waste can be processed, turning waste into treasure, and realizing green and energy-saving development.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a manganese-zinc ferrite material using industrial manganese sulfate waste comprises the following steps:
[0008] Mixing Fe2O3, industrial manganese sulfate waste and ZnO to obtain a mixed material;
[0009] Pre-burning the mixed material to obtain a pre-burned material; the pre-burning includes sequentially performing a first stage pre-burning and a second stage pre-burning, wherein the first stage pre-burning temperature is 800-900° C., the heat preservation time is 2-4 hours, and the second stage pre-burning temperature is 920-1000° C., the heat preservation time is 1-3 hours;
[0010] The pre-sintered material, water and additives are mixed and ball-milled to obtain a ball-milled slurry; the additives include SiO2, CaCO3, Nb2O5 and ZrO2;
[0011] The ball mill slurry and the polyvinyl alcohol solution are mixed and then granulated to obtain ferrite granules;
[0012] The ferrite particles are pressed and then sintered to obtain the manganese-zinc ferrite material; the sintering includes a first insulation sintering and a second insulation sintering in sequence; the first insulation sintering is performed at a temperature of 850 to 1000° C. for a insulation time of 2 to 6 hours, and the second insulation sintering is performed at a temperature of 1300 to 1350° C. for a insulation time of 3 to 6 hours.
[0013] Preferably, based on the total molar amount of the Fe2O3, industrial manganese sulfate waste and ZnO as 100%, the molar fraction of the Fe2O3 is 50-55%, the molar fraction of the industrial manganese sulfate waste is 31-38%, and the remainder is ZnO.
[0014] Preferably, the mixing time is 30 to 60 minutes.
[0015] Preferably, the mass of the SiO2 is 0.005-0.02% of the mass of the mixture, the mass of the CaCO3 is 0.02-0.05% of the mass of the mixture, the mass of the Nb2O5 is 0.01-0.05% of the mass of the mixture, and the mass of the ZrO2 is 0.02-0.04% of the mass of the mixture.
[0016] Preferably, the mass ratio of the pre-sintered material to the grinding balls used in ball milling is 1:5 to 1:10; and the ball milling time is 60 to 120 minutes.
[0017] Preferably, the concentration of the polyvinyl alcohol solution is 7-9 g / L; the mass of the polyvinyl alcohol solution is 0.05-0.1% of the mass of the mixture.
[0018] Preferably, the granulation is spray granulation, and the conditions of the spray granulation include: an inlet temperature of 290±10°C, an outlet temperature of 100±10°C, and a slurry pressure of 0.01-0.03MPa.
[0019] Preferably, the temperature rising program from room temperature to the temperature of the first heat preservation sintering is: firstly, the temperature is raised from room temperature to 400-450°C at a rate of 0.5-2°C / min, and then, the temperature is raised to the temperature of the first heat preservation sintering at a rate of 0.5-1°C / min; the temperature rising program from the temperature of the first heat preservation sintering to the temperature of the second heat preservation sintering is: firstly, the temperature is raised to 1150°C at a rate of 1-5°C / min, and then, the temperature is raised to the temperature of the second heat preservation sintering at a rate of 2-4°C / min.
[0020] Preferably, the sintering atmosphere is controlled in the sintering process as follows: in the stage of heating from room temperature to the temperature of the first insulation sintering, the sintering atmosphere is air; the oxygen partial pressure in the first insulation sintering stage is 1-5%, the oxygen partial pressure in the stage of heating from the first insulation sintering temperature to 1100°C is 1-3%, the oxygen partial pressure in the stage of heating from 1100°C to 1150°C is 0.5-1.5%, the oxygen partial pressure in the stage of heating from 1150°C to 1250°C is 1-3%, the oxygen partial pressure in the stage of heating from 1250°C to the temperature of the second insulation sintering is 2-2.5%, and the oxygen partial pressure in the second insulation sintering is 3-6%.
[0021] Preferably, after the second heat preservation sintering is completed, a cooling stage is further included; the cooling stage includes a first stage, a second stage, a third stage, a fourth stage and a fifth stage which are performed in sequence; the starting temperature of the first stage is the temperature of the second heat preservation sintering, the end temperature is 1250°C, the cooling rate of the first stage is 2-4°C / min, and the oxygen partial pressure is 1-3%; the starting temperature of the second stage is 1250°C, the end temperature is 1150°C, the cooling rate of the second stage is 1-3°C / min, and the oxygen partial pressure is 1-3%. min, and the oxygen partial pressure is 1-2%; the starting temperature of the third stage is 1150°C, the end temperature is 1050°C, the cooling rate of the third stage is 1-3°C / min, and the oxygen partial pressure is 0.5-1%; the starting temperature of the fourth stage is 1050°C, the end temperature is 1000°C, the cooling rate of the fourth stage is 1-2°C / min, and the oxygen partial pressure is 0.01-0.05%; the fifth stage is natural cooling starting from 1000°C, and the oxygen partial pressure is below 0.01%.
[0022] The invention provides a method for preparing a manganese-zinc ferrite material by using industrial manganese sulfate waste, comprising the following steps: mixing Fe2O3, industrial manganese sulfate waste and ZnO to obtain a mixture; pre-burning the mixture to obtain a pre-burned material; the pre-burning comprises sequentially performing a first-stage pre-burning and a second-stage pre-burning, wherein the temperature of the first-stage pre-burning is 800-900°C and the heat preservation time is 2-4 hours, and the temperature of the second-stage pre-burning is 920-1000°C and the heat preservation time is 1-3 hours; mixing the pre-burned material, water and an additive to obtain a spherical Grind to obtain ball mill slurry; the additives include SiO2, CaCO3, Nb2O5 and ZrO2; mix the ball mill slurry and polyvinyl alcohol solution and then granulate to obtain ferrite particles; press the ferrite particles and then sinter to obtain the manganese-zinc ferrite material; the sintering includes a first heat preservation sintering and a second heat preservation sintering in sequence; the temperature of the first heat preservation sintering is 850-1000°C, the heat preservation time is 2-6h, and the temperature of the second heat preservation sintering is 1300-1350°C, and the heat preservation time is 3-6h. The beneficial effects of the present invention are as follows:
[0023] In the pre-sintering stage, the present invention controls the pre-sintering temperature and time to convert all manganese sulfate into MnO2 and Mn3O4, and further adjusts the sintering temperature to make MnO2 and Mn3O4 react with iron oxide to form ferrite, thereby obtaining qualified ferrite pre-sintered material.
[0024] During the sintering process, the present invention first performs heat preservation treatment at 850-1000° C. to promote the removal of residual sulfate radicals, thereby avoiding abnormal grain growth and effectively improving product performance and qualified rate.
[0025] In summary, the present invention uses industrial manganese sulfate waste instead of manganese tetraoxide, and mixes it with industrial iron oxide and zinc oxide to prepare power manganese-zinc ferrite material, which solves the problem of difficult treatment of industrial manganese sulfate waste residue, reduces the production cost of power ferrite material, and improves market competitiveness. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a manganese-zinc ferrite material by utilizing industrial manganese sulfate waste, comprising the following steps:
[0027] Mixing Fe2O3, industrial manganese sulfate waste and ZnO to obtain a mixed material;
[0028] Pre-burning the mixed material to obtain a pre-burned material; the pre-burning includes sequentially performing a first stage pre-burning and a second stage pre-burning, wherein the first stage pre-burning temperature is 800-900° C., the heat preservation time is 2-4 hours, and the second stage pre-burning temperature is 920-1000° C., the heat preservation time is 1-3 hours;
[0029] The pre-sintered material, water and additives are mixed and ball-milled to obtain a ball-milled slurry; the additives include SiO2, CaCO3, Nb2O5 and ZrO2;
[0030] The ball mill slurry and the polyvinyl alcohol solution are mixed and then granulated to obtain ferrite granules;
[0031] The ferrite particles are pressed and then sintered to obtain the manganese-zinc ferrite material; the sintering includes a first insulation sintering and a second insulation sintering in sequence; the first insulation sintering is performed at a temperature of 850 to 1000° C. for a insulation time of 2 to 6 hours, and the second insulation sintering is performed at a temperature of 1300 to 1350° C. for a insulation time of 3 to 6 hours.
[0032] The present invention mixes Fe2O3, industrial manganese sulfate waste and ZnO to obtain a mixture. In the present invention, the industrial manganese sulfate waste is industrial manganese sulfate slag produced in the process of electrolytic manganese production; the content of manganese sulfate in the industrial manganese sulfate waste is preferably 98wt%; based on the total molar amount of the Fe2O3, industrial manganese sulfate waste and ZnO as 100%, the molar fraction of the Fe2O3 is preferably 50-55%, more preferably 52-53%, the molar fraction of the industrial manganese sulfate waste is preferably 31-38%, more preferably 32-36%, and the remainder is ZnO; the molar amount of the industrial manganese sulfate waste is calculated based on the molar amount of manganese sulfate contained therein; the mixing is preferably carried out in a mixer, and the mixing time is preferably 30-90min. The present invention ensures that the three raw materials are mixed evenly through mixing.
[0033] After obtaining the mixed material, the present invention pre-burns the mixed material to obtain the pre-burned material. In the present invention, the pre-burning includes sequentially performing a first stage pre-burning and a second stage pre-burning, the temperature of the first stage pre-burning is 800-900°C, preferably 830-860°C, the insulation time is 2-4h, preferably 2-3h, the temperature of the second stage pre-burning is 900-1000°C, preferably 930-960°C, the insulation time is 1-3h, preferably 1-2h; the pre-burning is preferably carried out in a muffle furnace; after the pre-burning is completed, the obtained pre-burned material is cooled. In the first stage of pre-calcination, manganese sulfate decomposes into MnO2 and Mn3O4, and ZnO reacts with the raw material Fe2O3 to form ZnFe2O4; in addition, SO2 gas is also generated during the decomposition of manganese sulfate. In the present invention, the generated SO2 gas is preferably dissolved in water for recycling and reuse, for example, the SO2 absorption liquid can be used in the preparation of fertilizers; in the second stage of pre-calcination, MnO2 and Mn3O4 formed by the decomposition of manganese sulfate react with the raw material Fe2O3 to form MnFe2O4, and the specific reaction formula is as follows:
[0034] MnO2(Mn3O4)+Fe2O3→MnFe2O4
[0035] After obtaining the pre-sintered material, the present invention mixes the pre-sintered material, water and additives for ball milling to obtain ball milling slurry; the additives include SiO2, CaCO3, Nb2O5 and ZrO2. In the present invention, the mass of the SiO2 is preferably 0.005-0.02% of the mass of the mixed material, more preferably 0.01-0.015%, the mass of the CaCO3 is preferably 0.02-0.05% of the mass of the mixed material, more preferably 0.03-0.04%, the mass of the Nb2O5 is preferably 0.01-0.05% of the mass of the mixed material, more preferably 0.03-0.04%, the mass of the ZrO2 is preferably 0.02-0.04% of the mass of the mixed material, more preferably 0.025-0.03%; the additives can increase the grain boundary resistivity of the material, reduce eddy current loss, and thus reduce overall loss.
[0036] In the present invention, the mass ratio of the pre-sintered material to the grinding balls used in ball milling is preferably 1:5 to 1:10, more preferably 1:5; the ball milling time is preferably 60 to 120 min, more preferably 80 to 100 min; and the ball milling is preferably carried out in a planetary ball mill.
[0037] After obtaining the ball mill slurry, the present invention mixes the ball mill slurry with a polyvinyl alcohol solution and then granulates to obtain ferrite particles. In the present invention, the concentration of the polyvinyl alcohol solution is preferably 7-9 g / L, more preferably 8 g / L; the mass of the polyvinyl alcohol solution is preferably 0.05-0.1% of the mass of the mixed material, more preferably 0.06-0.08%; the granulation is preferably spray granulation, and the conditions of the spray granulation preferably include: an inlet temperature of 290±10°C, an outlet temperature of 100±10°C, and a slurry pressure of 0.01-0.03 MPa; the spray granulation is preferably carried out using a small spray granulation device.
[0038] After obtaining the ferrite particles, the present invention presses the ferrite particles and then sintering them to obtain the manganese-zinc ferrite material. In the present invention, the pressing pressure is preferably 0.3-0.5 MPa; a green body is obtained by pressing. In a specific embodiment of the present invention, the green body is a standard sample ring with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 10 mm.
[0039] In the present invention, the sintering includes a first insulation sintering and a second insulation sintering in sequence; the temperature of the first insulation sintering is 850-1000°C, preferably 900-950°C, and the insulation time of the first insulation sintering is preferably 2-6h, more preferably 3-5h; the temperature of the second insulation sintering is 1300-1350°C, preferably 1320-1330°C, and the insulation time of the second insulation sintering is preferably 3-6h, more preferably 4-5h.
[0040] In the present invention, the temperature rising procedure from room temperature to the temperature of the first heat preservation sintering is preferably: firstly, the temperature is raised from room temperature to 400-450°C at a rate of 0.5-2°C / min, and then, the temperature is raised to the first heat preservation sintering temperature at a rate of 0.5-1°C / min. More preferably, the temperature is raised from room temperature to 420-430°C at a rate of 1-1.5°C / min, and then, the temperature is raised to the first heat preservation sintering temperature at a rate of 0.5-0.8°C / min. The temperature rising procedure from the temperature of the first heat preservation sintering to the temperature of the second heat preservation sintering is preferably: firstly, the temperature is raised to 1150°C at a rate of 1-5°C / min, and then, the temperature is raised to the second heat preservation sintering temperature at a rate of 2-4°C / min. More preferably, the temperature is raised to 1150°C at a rate of 2-3°C / min, and then, the temperature is raised to the second heat preservation sintering temperature at a rate of 2.5-3.5°C / min. In the present invention, a large amount of sulfate ion impurities are generated during the pre-sintering process of manganese sulfate. After the ferrite blank is prepared, part of the sulfate remains in the blank, which may cause abnormal growth of the grains of the final magnetic core product. During sintering, the present invention fully removes the residual sulfate through the first heat-insulating sintering to ensure that the grains will not grow abnormally in the subsequent sintering, thereby ensuring the performance of the magnetic core; during the second heat-insulating sintering process, the ferrite grains grow, and at the same time, the pores move along the grain boundaries to the surface of the material for discharge, and the impurities such as SiO2, CaO, Nb2O5 added to the ferrite move and segregate to the grain boundaries to form an insulating layer with high resistivity, thereby reducing the power consumption characteristics of the material. Through heat preservation, the atoms of the components constituting the ferrite material are rearranged to form a spinel structure with fewer pore defects and orderly arrangement, which is crucial to the material performance.
[0041] In the present invention, the control method of the sintering atmosphere during the sintering process is preferably: in the stage of heating from room temperature to the temperature of the first heat preservation sintering, the sintering atmosphere is preferably air; the oxygen partial pressure in the first heat preservation sintering stage is preferably 1-5%, more preferably 1-4%, the oxygen partial pressure in the stage of heating from the first heat preservation sintering temperature to 1100°C is preferably 1-3%, more preferably 1-2%, the oxygen partial pressure in the stage of heating from 1100°C to 1150°C is preferably 0.5-1.5%, more preferably 1%, the oxygen partial pressure in the stage of heating from 1150°C to 1250°C is preferably 1-3%, more preferably 1.5-2.5%, the oxygen partial pressure in the stage of heating from 1250°C to the temperature of the second heat preservation sintering is preferably 2-2.5%, more preferably 2%, and the oxygen partial pressure in the second heat preservation sintering is preferably 3-6%, more preferably 3-5%. The present invention controls the oxygen partial pressure during the sintering process, which can ensure that the Fe inside the material is 2+ / Fe 3+ The right proportion optimizes material performance.
[0042] In the present invention, after the second heat preservation sintering is completed, it is preferred to further include a cooling stage; the cooling stage preferably includes a first stage, a second stage, a third stage, a fourth stage and a fifth stage performed in sequence; the starting temperature of the first stage is preferably the temperature of the second heat preservation sintering (i.e., 1300-1350°C), the end temperature is preferably 1250°C, the cooling rate of the first stage is preferably 2-4°C / min, more preferably 2-3°C / min, and the oxygen partial pressure is preferably 1-3%, more preferably 1.5-2%; the starting temperature of the second stage is preferably 1250°C, the end temperature is preferably 1150°C, the cooling rate of the second stage is preferably 1-3°C / min, more preferably 2°C / min, and the oxygen partial pressure is preferably 1.5-2%. The partial pressure is preferably 1-2%, more preferably 1.5%; the starting temperature of the third stage is 1150°C, the end temperature is 1050°C, the cooling rate of the third stage is preferably 1-3°C / min, more preferably 1°C / min, and the oxygen partial pressure is preferably 0.5-1%, more preferably 0.5-0.8%; the starting temperature of the fourth stage is preferably 1050°C, the end temperature is preferably 1000°C, the cooling rate of the fourth stage is preferably 1-2°C / min, more preferably 1-1.5°C / min, and the oxygen partial pressure is preferably 0.01-0.05%, more preferably 0.01-0.03%; the fifth stage is natural cooling starting from 1000°C, and the oxygen partial pressure is preferably below 0.01%.
[0043] In a specific embodiment of the present invention, the amount of nitrogen and air entering the sintering device is preferably controlled by a computer program, and the oxygen partial pressure in the sintering atmosphere is controlled by the ratio of nitrogen to air.
[0044] In the present invention, during the sintering process, manganese-zinc ferrite forms spinel structure FeFe2O4 and MnFe2O4, wherein Fe 2 + , Mn 2+ It is a variable valence element. Under the condition of high oxygen content, FeFe2O4 and MnFe2O4 will undergo oxidation reaction and become Fe2O3 and Mn2O3 with non-spinel structure, which will seriously deteriorate the material properties. The present invention controls different oxygen partial pressures at different stages of cooling to avoid oxidation of FeFe2O4 and MnFe2O4 that have been formed, so that these two components are maintained until the end of sintering, ensuring that the material properties are appropriate.
[0045] In the present invention, preferably, five green bodies obtained by pressing are stacked together and sintered in a fully automatic atmosphere-controlled bell-shaped furnace.
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The industrial manganese sulfate waste used in the embodiment is industrial manganese sulfate slag produced in the electrolytic manganese production process.
[0048] Example 1
[0049] (1) Calculated by molar percentage, the composition of the raw materials is: Fe2O3 53.5 mol%, industrial manganese sulfate waste (wherein the content of manganese sulfate is 98 wt%), 35 mol%, and the balance is ZnO. The three raw materials are weighed and mixed in a mixer for 90 min to ensure that the three raw materials are evenly mixed to obtain a mixture.
[0050] (2) The mixed material is placed in a muffle furnace for pre-calcination. The temperature is first raised to 850°C and kept at this temperature for 3 hours. At this time, manganese sulfate decomposes into MnO2 and Mn3O4, and the SO2 produced by the decomposition is recovered for further treatment. The temperature is then raised to 1000°C and kept at this temperature for 3 hours. The MnO2 and Mn3O4 formed by the decomposition of manganese sulfate react with the raw material Fe2O3 to form MnFe2O4, thereby obtaining the pre-calcined material.
[0051] (3) After the pre-sintered material is cooled, it is placed in a planetary ball mill together with grinding balls, and water and additives are added to grind and crush the material to obtain a ball-milled slurry; wherein the weight ratio of the pre-sintered material, water and grinding balls is 1:1:5, the ball milling time is 60 min, and the amount of each additive added, based on the mass percentage of each additive in the mixed material, is: SiO2: 0.005wt%, CaCO3: 0.05wt%, Nb2O5: 0.05wt%, ZrO2: 0.02wt%.
[0052] (4) Add polyvinyl alcohol solution (the concentration of polyvinyl alcohol solution is 8 g / L, and the amount added is 0.05 wt% of the weight of the mixed material) to the obtained ball mill slurry, and then granulate the obtained slurry using a small spray granulation equipment to obtain ferrite particles. Spray granulation inlet temperature: 290°C, outlet temperature: 100°C, slurry pressure: 0.03 MPa.
[0053] (5) The ferrite particles are pressed into a standard sample ring with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 10 mm.
[0054] (6) Stack the pressed standard sample rings in 5 pieces and sinter them in a fully automatic atmosphere controlled bell furnace. The specific sintering operation is as follows: heat up to 450°C at a rate of 0.5°C / min, with air as the atmosphere, then heat up to 1000°C at a rate of 1°C / min, keep warm for 3 hours, then adjust the heating rate to 5°C / min, heat up to 1150°C, and finally heat up to 1320°C at a rate of 4°C / min, keep warm for 6 hours. During the heating process: the sintering atmosphere in the stage from room temperature to 1000°C is air, the oxygen partial pressure in the 1000°C insulation stage is controlled at 5%, the oxygen partial pressure in the stage from 1000°C to 1100°C is controlled at 1%, the oxygen partial pressure in the stage from 1100°C to 1150°C is controlled at 0.5%, the oxygen partial pressure in the stage from 1150°C to 1250°C is controlled at 1.5%, the oxygen partial pressure in the stage from 1250°C to 1320°C is controlled at 2%, and the oxygen partial pressure in the 1320°C insulation section is 3%.
[0055] After the insulation at 1320℃ was completed, the temperature began to cool down. The cooling rate from 1320 to 1250℃ was 2℃ / min, and the oxygen partial pressure was controlled at 1.5%; the cooling rate from 1250℃ to 1150℃ was controlled at 1℃ / min, and the oxygen partial pressure was controlled at 1%; the cooling rate from 1150℃ to 1050℃ was controlled at 1℃ / min, and the oxygen partial pressure was controlled at 0.5%; the cooling rate from 1050℃ to 1000℃ was 1℃ / min, and the oxygen partial pressure was controlled at 0.01%; the temperature was naturally cooled below 1000℃, and the oxygen partial pressure was controlled below 0.01%.
[0056] The sintered sample ring was taken out, and the power consumption and saturation magnetic flux density Bs of the sample ring were tested by Iwasaki SY8218B-H analyzer at 100KHz and 200mT, the density of the sample ring was tested by the drainage method, and the initial magnetic permeability of the sample ring was tested by Agilent HP4294A high-frequency impedance analyzer. The test performance of the sintered sample ring obtained in Example 1 is shown in Table 1:
[0057] Table 1 Sintered ring performance test results
[0058]
[0059] It can be seen from the data in Table 1 that the manganese-zinc ferrite prepared by the present invention has high initial magnetic permeability, small volume power consumption, high saturation magnetic flux density and excellent performance.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing manganese-zinc ferrite material using industrial manganese sulfate waste, characterized in that: The following steps are involved: Mixing Fe2O3, industrial manganese sulfate waste and ZnO to obtain a mixed material; Pre-burning the mixed material to obtain a pre-burned material; the pre-burning includes sequentially performing a first stage pre-burning and a second stage pre-burning, wherein the first stage pre-burning temperature is 800-900° C., the heat preservation time is 2-4 hours, and the second stage pre-burning temperature is 920-1000° C., the heat preservation time is 1-3 hours; The pre-sintered material, water and additives are mixed and ball-milled to obtain a ball-milled slurry; the additives include SiO2, CaCO3, Nb2O5 and ZrO2; The ball mill slurry and the polyvinyl alcohol solution are mixed and then granulated to obtain ferrite granules; The ferrite particles are pressed and then sintered to obtain the manganese-zinc ferrite material; the sintering includes a first insulation sintering and a second insulation sintering in sequence; the first insulation sintering is performed at a temperature of 850 to 1000° C. for a insulation time of 2 to 6 hours, and the second insulation sintering is performed at a temperature of 1300 to 1350° C. for a insulation time of 3 to 6 hours.
2. The method according to claim 1, characterized in that Taking the total molar amount of the Fe2O3, industrial manganese sulfate waste and ZnO as 100%, the molar fraction of the Fe2O3 is 50-55%, the molar fraction of the industrial manganese sulfate waste is 31-38%, and the remainder is ZnO.
3. The method according to claim 1, characterized in that: The mixing time is 30 to 60 minutes.
4. The method according to claim 1, characterized in that: The mass of the SiO2 is 0.005-0.02% of the mass of the mixture, the mass of the CaCO3 is 0.02-0.05% of the mass of the mixture, the mass of the Nb2O5 is 0.01-0.05% of the mass of the mixture, and the mass of the ZrO2 is 0.02-0.04% of the mass of the mixture.
5. The method according to claim 1, characterized in that The mass ratio of the pre-sintered material to the grinding balls used for ball milling is 1:5 to 1:10; and the ball milling time is 60 to 120 minutes.
6. The method according to claim 1, characterized in that The concentration of the polyvinyl alcohol solution is 7-9 g / L; the mass of the polyvinyl alcohol solution is 0.05-0.1% of the mass of the mixed material.
7. The method according to claim 1, characterized in that The granulation is spray granulation, and the conditions of the spray granulation include: an inlet temperature of 290±10°C, an outlet temperature of 100±10°C, and a slurry pressure of 0.01-0.03MPa.
8. The method according to claim 1, characterized in that The temperature rising program from room temperature to the temperature of the first heat preservation sintering is: firstly, the temperature is raised from room temperature to 400-450°C at a rate of 0.5-2°C / min, and then, the temperature is raised to the temperature of the first heat preservation sintering at a rate of 0.5-1°C / min; the temperature rising program from the temperature of the first heat preservation sintering to the temperature of the second heat preservation sintering is: firstly, the temperature is raised to 1150°C at a rate of 1-5°C / min, and then, the temperature is raised to the temperature of the second heat preservation sintering at a rate of 2-4°C / min.
9. The method according to claim 8, characterized in that The control method of the sintering atmosphere during the sintering process is: in the stage of heating from room temperature to the temperature of the first heat-insulating sintering, the sintering atmosphere is air; the oxygen partial pressure in the stage of heating from the temperature of the first heat-insulating sintering to 1100°C is 1-3%, the oxygen partial pressure in the stage of heating from 1100°C to 1150°C is 0.5-1.5%, the oxygen partial pressure in the stage of heating from 1150°C to 1250°C is 1-3%, the oxygen partial pressure in the stage of heating from 1250°C to the temperature of the second heat-insulating sintering is 2-2.5%, and the oxygen partial pressure in the second heat-insulating sintering is 3-6%.
10. The method according to claim 1, 8 or 9, characterized in that: After the second heat preservation sintering is completed, it also includes a cooling stage; the cooling stage includes the first stage, the second stage, the third stage, the fourth stage and the fifth stage which are carried out in sequence; the starting temperature of the first stage is the temperature of the second heat preservation sintering, the end temperature is 1250°C, the cooling rate of the first stage is 2-4°C / min, and the oxygen partial pressure is 1-3%; the starting temperature of the second stage is 1250°C, the end temperature is 1150°C, and the cooling rate of the second stage is 1-3°C / min. n, the oxygen partial pressure is 1-2%; the starting temperature of the third stage is 1150°C, the end temperature is 1050°C, the cooling rate of the third stage is 1-3°C / min, and the oxygen partial pressure is 0.5-1%; the starting temperature of the fourth stage is 1050°C, the end temperature is 1000°C, the cooling rate of the fourth stage is 1-2°C / min, and the oxygen partial pressure is 0.01-0.05%; the fifth stage is natural cooling starting from 1000°C, and the oxygen partial pressure is below 0.01%.
Citation Information
Patent Citations
Method for preparing soft magnetic manganese-zinc-iron composite material by using manganese-containing waste liquor and zinc sludge produced during production of p-dihydroxybenzene
CN104086168A
Preparation method of manganese zinc soft magnetic ferrite
CN107827448A
Wide-temperature-range ultralow-power-consumption manganese-zinc ferrite material and preparation method thereof
CN112707723A
Cold and hot shock resistant low-loss manganese-zinc power ferrite magnetic core and preparation method thereof
CN116693282A
Method of preparing high-purity manganomanganic oxide by pyrolyzing manganese sulfate at high temperature
CN1927727A
Cited By
Manganese zinc ferrite as well as preparation method and application thereof
CN121085623A
